Implementasi Kebijakan Pesantren Ashri Jember dalam Menolak Keberadaan Hypermarket: Implementation of the Policy of Ashri Islamic Boarding School in Jember to Reject the Presence of a Hypermarket - Nurul Widyawati Islami Rahayu (Fenomena, 2014)
From its early establishment, Islamic boarding schools were built to preserve and maintain medieval Islamic values as a guide for the religious behavior of their followers. Generally, Islamic boarding schools teach honesty, sincerity, and willingness. These values are the soul of all activities in Islamic boarding schools, including at Ashri Islamic Boarding School, Talangsari Jember. This boarding school, known as the Talangsari Female Islamic Boarding School, always emphasizes and prioritizes devotion and sincerity. All workers in the economic sector are required to purify their intentions and dedicate themselves to the boarding school. Devotion is synonymous with working selflessly, without calculating the benefits to be gained. Sejak awal berdirinya, pesantren dibangun untuk merawat dan melestarikan nilai-nilai keislaman abad pertengahan sebagai pedoman perilaku keberagamaan umat. Secara umum, pesantren mengajarkan kejujuran, ketulusan, dan kerelaan. Nilai-nilai tersebut menjadi jiwa dari seluruh aktivitas pesantren, termasuk di Pesantren Ashri Talangsari Jember. Pesantren yang dikenal sebagai Pesantren Putri Talangsari ini selalu menekankan dan mengutamakan pengabdian dan ketulusan. Seluruh karyawan di sektor ekonomi diwajibkan untuk memurnikan niat, berkorban demi pesantren. Pengabdian identik dengan bekerja tanpa pamrih, tidak menghitung keuntungan yang akan diperoleh.